Model Integratif Pembentukan Karakter Peserta Didik melalui Kegiatan Rohani di SMK Negeri Ndora - Albertus Policarpus Dedon (MASALIQ, 2026)
Student character formation requires an approach that not only emphasizes the understanding of values but also integrates spiritual experiences, reflection, and habituation into school life. This study aimed to analyze the contribution of spiritual activities to student character formation at SMK Negeri Ndora and to develop an integrative character formation model based on six spiritual activities. The study employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving a Catholic Religious Education teacher, the vice principal for student affairs, and eleventh-grade students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that character formation occurred through the integration of six spiritual activities, namely reading Scripture, prayer, Scripture sharing, fasting or matiraga, Eucharistic celebrations, and retreats or recollections. Each activity had a distinct yet complementary pedagogical mechanism. Reading Scripture fostered moral awareness; prayer strengthened discipline, self-regulation, spirituality, and emotional management; Scripture sharing developed empathy and communication skills through reflective dialogue; fasting fostered self-control and social concern; Eucharistic celebrations strengthened the internalization of values through liturgical reflection; while retreats or recollections consolidated spiritual experiences into a moral identity manifested in everyday behavior. This study produced an Integrative Character Formation Model Based on Six Spiritual Activities comprising three stages, namely value internalization, social transformation, and moral identity consolidation. The model contributes theoretically to the development of character education and can serve as an alternative for implementing spirituality-based character education in school settings.